The Effect of Investment Knowledge 0n Investment Interest Through The Mediating Role of Investment Risk Perception Among Gen Z Communities in Pematangsiantar City - Mahaitin H Sinaga; Desmi Triyanti Purba; Liper Siregar; Sepbeariska Manurung (Jurnal Ilmiah Accusi, 2026)
This study examines the effect of investment knowledge on investment interest among Gen Z communities in Pematangsiantar City, with investment risk perception positioned as a mediating variable. Gen Z represents a productive demographic group with substantial potential to participate in investment activities; however, this potential must be supported by adequate investment knowledge and a rational understanding of investment risk. This study employed a quantitative research approach using primary data collected through questionnaires and interviews with 60 respondents. The respondents were selected using purposive sampling, with the sample limited to Gen Z individuals residing in Pematangsiantar City. The data were analyzed through validity testing, reliability testing, normality testing, coefficient of determination analysis, and hypothesis testing. The findings reveal that investment knowledge has a positive and significant effect on investment interest. Investment knowledge also has a negative and significant effect on investment risk perception, while investment risk perception has a negative and significant effect on investment interest. Furthermore, the results confirm that investment risk perception mediates the relationship between investment knowledge and investment interest. These findings imply that higher investment knowledge may strengthen investment interest both directly and indirectly by reducing excessive perceptions of investment risk among Gen Z communities